2015
DOI: 10.1038/pr.2015.234
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to bisphenol-A is associated with Toll-like receptor–induced cytokine suppression in neonates

Abstract: Background: Despite widespread human exposure to biphenol A (BPA), limited studies exist on the association of BPA with adverse health outcomes in young children. This study aims to investigate the effect of prenatal exposure to BPA on toll-like receptor-induced cytokine responses in neonates and its association with infectious diseases later in life. Methods: Cord bloods were collected from 275 full-term neonates. Production of TNF-α, IL-6, and IL-10 were evaluated after stimulating mononuclear cells with tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Therefore, alterations in expression patterns of these cytokines indicate that parental exposure to bisphenols immunosuppresses F1 larvae. Prenatal exposure to BPA is shown to be associated with TLR-induced cytokine suppression, such as TNFα, in neonates (Liao et al, 2016). High pathogen load, coupled with reductions in important antibacterial and antiviral cytokines, as was modeled here, using bisphenols and zebrafish, may blunt offspring immunity and prevent a competent immune response vital for eradicating infection.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, alterations in expression patterns of these cytokines indicate that parental exposure to bisphenols immunosuppresses F1 larvae. Prenatal exposure to BPA is shown to be associated with TLR-induced cytokine suppression, such as TNFα, in neonates (Liao et al, 2016). High pathogen load, coupled with reductions in important antibacterial and antiviral cytokines, as was modeled here, using bisphenols and zebrafish, may blunt offspring immunity and prevent a competent immune response vital for eradicating infection.…”
Section: Discussionmentioning
confidence: 87%
“…Then, we used a disease challenge to assess the integrated immune system response and measured gene expression for those genes responsible for eliminating invading pathogens. We selected the following genes that are expressed exclusively in the immune system: toll-like receptors (TLRs) and downstream signaling molecule mRNA such as myeloid differentiation factor 88 (MyD88), Toll/IL-1 receptor domain-containing adaptor inducing IFN-β (TRIF), inflammatory cytokines including type I interferon (IFN), myxovirus-resistance gene (Mx), tumor necrosis factor α (TNFα) and interleukin-1β (IL-1β), and matrix metalloproteinases (MMP) (Li et al, 2017;Liao et al, 2016;Medzhitov, 2001). Oxidative defense is involved in immune response (Biller-Takahashi et al, 2015), so myeloperoxidase (MPX), and superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) mRNA expression was measured.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…No other studies have examined the effect of these plasticizing chemicals on Th1 and Th2 function in childhood, and only a small number have examined prenatal exposure and cytokine function in cord blood. One study found no association between prenatal maternal urinary concentrations of or BPA and cord blood Th2 cytokine concentrations in infants, while another found an association between prenatal maternal blood concentrations of BPA and higher Th2 cytokines in cord blood. However, T helper cell‐related immunity changes drastically from birth to age 2, and these previous studies may not be appropriate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The potentiating effect of histamine action by BPA might play a crucial role in BPA-induced inflammatory process. [20] A recent report [21] indicated that BPA inhibits movements of rat duodenum through NO-mediated mechanisms. However, whether the similar NO mechanisms are involved in ileum and colon needs further investigation.…”
Section: Discussionmentioning
confidence: 99%